1977
DOI: 10.1002/pssb.2220790238
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the electrical conductivity and hall coefficient in 2H‐MoS2, MoSe2, WSe2, and MoTe2

Abstract: The electrical conductivity and Hall coefficient perpendicular to the c-axis of hexagonal MoS,, MoSe,, and WSe, are measured over the temperature ranges 120 to 117OK and 140 to 820K, respectively. The derived temperature-dependent carrier densities are described by nexp (-E/IcT) for temperatures less than 800 K indicating (thermal) energy gaps of 0.38 eV in n-type MoS,, 0.27 eV in n-type MoSe,, and 0.19 eV in p-type WSe,. Above room temperature the carrier mobilities are given by p -T-a, where a z 1.5 in MoS,,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 22 publications
10
84
2
Order By: Relevance
“…From the electronic structure it is possible to calculate s/t as a function of temperature (T) and carrier concentration (n), but it is not possible to calculate s without relaxation time (t). To approximate the relaxation time, we used experimental data from Mahalaway et al 65 The reported experimental electrical conductivity is 0.03 O À 1 cm À 1 at room temperature, which combined with the calculated s/t yield t ¼ 7.5  10 À 14 . We then calculate s as s/t  t.…”
Section: Methodsmentioning
confidence: 99%
“…From the electronic structure it is possible to calculate s/t as a function of temperature (T) and carrier concentration (n), but it is not possible to calculate s without relaxation time (t). To approximate the relaxation time, we used experimental data from Mahalaway et al 65 The reported experimental electrical conductivity is 0.03 O À 1 cm À 1 at room temperature, which combined with the calculated s/t yield t ¼ 7.5  10 À 14 . We then calculate s as s/t  t.…”
Section: Methodsmentioning
confidence: 99%
“…The small rate of change of conductivity with pressure meant that the isobaric conduct,ivity versus temperature graphs, The WSe, isobaric conductivity versus temperature graphs, Fig. 5, resemble the atmospheric pressure conductivity graphs which, as for MoS,, could be measured over a much wider temperature range [6]. The graphs of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Below 800 K the measured activation energies of electrical conduction depend strongly upon the method of crystal growth, consequently conduction at these temperatures hae been attributed to extrinsic processes, particularly since impurities are so readily incorporated between the crystal layers. However, recent measurements on crystals grown directly from the powdered constituents (instead of using the mineral or crystal grown by halogen transport) have given consistent values for the activation eriergy of conduction, corresponding to energy gaps of 0.47 eV in n-type 2H-MoS2 and 0.17 eV in p-type 2H-WSe2 [6]. While these values may correspond to the presence of a specific impurity in each case it is also possible that the energy gaps may be an intrinsic property of the MoS, and WSe, crystals.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations